"Now, I am Empowered. Now, I am a Woman With Spirit": Evaluating CARE's Public Health Work Through a Community-Organizing Framework in Sri Lanka and Bangladesh. (April 2021) - Saxon, Andrew; Ford, Jessie V.
Community-based interventions are crucial to reducing health-care disparities throughout the world. CARE, an international development nongovernmental organization (NGO), is a global leader in using a community-based approach in public health. This qualitative study sought to understand the processes through which community organizing functions to effectively facilitate change and improve health among underserved populations in three programs in Sri Lanka and Bangladesh. Sixteen in-depth interviews and two focus groups were conducted with NGO staff, partner organization staff, and community change agents. Programs are assessed through Ganz's community-organizing model, which includes (a) leadership development, (b) storytelling strategies, and (c) team building. Our findings confirm existing literature showing that public health approaches can be augmented by using community organizing to develop local engagement. Results show that program success relates to developing community members' understanding of social inequality and its impact on society. Other important strategies include systems strengthening, political engagement, coalition building, and government outreach. Empowered communities were created through recruiting, activating, and investing in community members, their stories, and their collaborative potential, at least in the sites studied here. Collectively, these programs have begun to create empowered communities among some of the most marginalized people in Sri Lanka and Bangladesh.